2012
DOI: 10.1016/j.brainres.2011.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone differentially modulates the cortisol response of the hypothalamic–pituitary–adrenal axis in male and female rhesus macaques, and restores circadian secretion of cortisol in females

Abstract: Here we used a within-subject design to evaluate hypothalamic-pituitary-adrenal (HPA) activity following replacement of low and high physiological levels of testosterone (T) to adult, gonadally-suppressed, male rhesus macaques, and replacement with sex-specific low and high physiological doses of dihydrotestosterone (DHT) in the same adult males as well as in adult, gonadally-suppressed, female rhesus macaques. As indexes of HPA axis activation following T and DHT replacement, serum levels of cortisol (CORT) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
1
14
1
Order By: Relevance
“…Specifically, an intravenous CRF challenge increases cortisol levels more in female than male rhesus monkeys and common marmosets [61,62]. This sex difference is linked to dihydrotestosterone, which reduces CRF-stimulated cortisol release in male monkeys [63]. Although these findings suggest sex differences in CRF sensitivity, the CRF challenge in marmosets did not increase ACTH levels more in females than males, suggesting sex differences in the adrenal response to ACTH in this species [62].…”
Section: Sex Differences In Crf-mediated Responses To Stresscontrasting
confidence: 48%
“…Specifically, an intravenous CRF challenge increases cortisol levels more in female than male rhesus monkeys and common marmosets [61,62]. This sex difference is linked to dihydrotestosterone, which reduces CRF-stimulated cortisol release in male monkeys [63]. Although these findings suggest sex differences in CRF sensitivity, the CRF challenge in marmosets did not increase ACTH levels more in females than males, suggesting sex differences in the adrenal response to ACTH in this species [62].…”
Section: Sex Differences In Crf-mediated Responses To Stresscontrasting
confidence: 48%
“…This effect has been shown in multiple species including primates (Toufexis and Wilson, 2012). In order to demonstrate that the elevation in stress-reactive CORT secretion following orchidectomy occurs within a timeframe that was amenable to study by pharmacological blockade of 5αR, we first identified the time course for the gonadectomy effect.…”
Section: Discussionmentioning
confidence: 73%
“…Depending on dose, timing, or age of treatment, estradiol (E) treatment of gonadectomized animals can either enhance or inhibit (Serova et al, 2010, Evuarherhe et al, 2009, Weiser and Handa, 2009, Young et al, 2001) HPA activity, whereas androgen treatment has consistently been shown to inhibit HPA reactivity in rodents, monkeys and humans (Kalil et al, 2013, Williamson and Viau, 2008, Handa et al, 1994b, Toufexis and Wilson, 2012, Rubinow et al, 2005). To date, the mechanism(s) by which T and E act to influence HPA function have not been completely resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is abundant evidence supporting a role of estrogen both in increasing and decreasing HPA axis activity through alteration of GR signaling pathways (Burgess and Handa 1992, Weiser and Handa 2009, Weiser et al 2010). Moreover, androgens are also known to decrease HPA axis activity by reducing glucocorticoid secretion (Toufexis and Wilson 2012, Kalil et al 2013). Additionally, interactions between the estrogen/androgen receptors and GR exist (Miranda et al 2013, Lightman and George 2014) that may contribute to the observed sex differences.…”
Section: Discussionmentioning
confidence: 99%